دور الرقمنة في تحسين فعالية الإدارة العمومية وتطوير التسيير الاداري -دراسة ميدانية ببلدية خميس مليانة- - طرشاني سهام; بن زيدان فاطمة الزهرة; بوكدرون يوسف (جامعة الواديUniversity of Eloued, 2024)
تهدف هذه الدراسة الى توضيح مساهمة الرقمنة في تحسين فعالية الإدارة العمومية وتطوير التسيير العمومي للخدمات ببلدية خميس مليانة ، وذلك بعرض أهم الدراسات السابقة التي لها صلة بالموضوع ومن ثم حاولنا إسقاط الدراسة على الواقع، قمنا بتوزيع 35 استبانه على الموظفين في المؤسسة محل الدراسة . ومن أجل تحقيق أهداف الدراسة قام الباحثون باستخدام المنهج الوصفي التحليلي الذي يحاول من خلاله وصف الظاهرة موضوع الدراسة، وتحليل بياناتها، والعلاقة بين مكوناتها والآراء التي تطرح حولها، ومن اجل ذلك تم استخدام طريقة الحصر الشامل نظرا لصغر حجم مجتمع الدراسة وسهولة ً الوصول إلى الفئة المستهدفة. كما توصلنا إلى مجموعة من النتائج نذكر منها أن هناك علاقة ذات دلالة إحصائية بين كل من تكنولوجيا الاتصال، قواعد البيانات، مصادر المعلومات، المتدخلون والشبكات في تحسين التسيير العمومي ببلدية خميس مليانة. This article aims to clarify the contribution of digitization in improving the effectiveness of public administration and developing the public management of services in the municipality of Khemis Miliana, by presenting the most important previous studies related to the topic. Then we tried to project the study onto reality. We distributed 35 questionnaires to employees in the institution under study and to analyze its data, the relationship between its components and the opinions expressed about it. For this purpose, the comprehensive inventory method was used due to the small size of the study population and the ease of reaching the target group. We also reached a set of results, including that there is a statistically significant relationship between communication technology, databases, information sources, stakeholders and networks in improving public management in the municipality of Khemis Miliana.
The role of digitization in improving the effectiveness of public administration and developing administrative management- A field study in the municipality of Khamis Miliana
Keywords: الادارة الرقمية، التسيير الاداري، قواعد البيانات، بلدية خميس مليانة.